Hubungan Perilaku Merokok dengan Kejadian Hipertensi di Desa Saentis - Eli Marlina Lubis; Yolanda Afifah; Farah Amira Abidin; M. Daffa Ash Shiddiq; Zatta Ismah (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The main results of the 2018 Basic Health Research (Riskesdas), the prevalence of hypertension in Indonesia is 34.1%. This is an increase compared to the 2013 Riskesdas prevalence of hypertension, which was 25.8%. This figure is quite high which makes Indonesia's percentage ranked 5th most cases of hypertension in the world. The prevalence of hypertension in North Sumatra reaches 5.52% of the total population in North Sumatra. While the prevalence of hypertension in Medan City is 4.97%. Based on data from the Indonesian Ministry of Health (2018), the prevalence of hypertension according to sex where the prevalence of women with hypertension is 36.85% and men are 31.34%. In this case the prevalence of women is greater than men. Based on data from the health profile of North Sumatra Province, the prevalence of high blood pressure in 2019 was dominated by men (32.28%) higher than women (31.68%). The purpose of this study was to determine the relationship between smoking behavior and the incidence of hypertension in Saentis Village. This research is a quantitative study with a cross-sectional study design with the aim of knowing the relationship between smoking behavior and the incidence of hypertension. Based on the results of the study, it was found that there was no relationship between smoking behavior and the incidence of hypertension in Saentis Village